Karakteristik dan Implementasi Kurikulum Muatan Lokal dalam Kaitannya dengan Perkembangan Kebutuhan Masyarakat - Enco Mulyasa (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
The Characteristics and the Implementation of Local Content Curriculum in Relation to the Development of Society’s Needs. The Study aimed to describe the characteristics and the implementation of local content curriculum in relation to the society’s needs. Qualitative research design was employed with documents, teachers, and informal leaders as sources of research data. The data were collected by means of observation, interview, and documentation techniques and were then analyzed by reduction, display, and verification, which was done throughout the study. The results showed that the local content curriculum was not optimally implemented yet and that there was a gap between local content curriculum and the needs of the local society.